2017
DOI: 10.1007/s00421-017-3592-2
|View full text |Cite
|
Sign up to set email alerts
|

The independent influences of heat strain and dehydration upon cognition

Abstract: These observations imply that, once potentially confounding influences were controlled, moderate hyperthermia, significant dehydration and their combined effects had insufficient impact to impair cognition within the memory and perceptual domains tested. Nonetheless, moderate hyperthermia elicited more liberal and rapid responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…The stepwise linear regression showed that from changes in subjective and physiological measures only change in gastrointestinal temperature explained the change in reaction times. This is in line with Heuvel et al showing more liberal and quick responses when gastrointestinal temperature is elevated [18]. In addition, Van Maanen et al, 2019, showed that the shorter response times are explained by the effect of lowering the information decision threshold (for more information on decision thresholds see [10,21,22]).…”
Section: Change In Response Timesupporting
confidence: 75%
See 2 more Smart Citations
“…The stepwise linear regression showed that from changes in subjective and physiological measures only change in gastrointestinal temperature explained the change in reaction times. This is in line with Heuvel et al showing more liberal and quick responses when gastrointestinal temperature is elevated [18]. In addition, Van Maanen et al, 2019, showed that the shorter response times are explained by the effect of lowering the information decision threshold (for more information on decision thresholds see [10,21,22]).…”
Section: Change In Response Timesupporting
confidence: 75%
“…In terms of response times, results showed that response times are shortened in the warm condition compared to the neutral condition which is in line with [6,10,18,19]. In part, faster response times can be explained by increased synaptic activity and faster muscle cross-bridge cycling which are associated with increased tissue temperature (Arrhenius law or Q10 effect) [19,20]; nevertheless, a main effect of time showed that the duration of the experiment and time in the water further decreased the response times in both neutral and warm condition -hence also indicating an independent effect on response time.…”
Section: Change In Response Timesupporting
confidence: 72%
See 1 more Smart Citation
“…On the other hand, no effects on cognitive performance (executive function, choice reaction, vigilance etc.) have been reported across a series of studies [ 7 , 8 , 31 , 32 , 36 39 ], although the dehydration-levels were comparable to the above-mentioned studies and the participants’ mood and wellness were negatively affected when participants were dehydrated [ 7 , 10 , 31 ].…”
Section: Introductionmentioning
confidence: 70%
“…High fever and hypovolemia often develop simultaneously in a thermal environment [24]. Passive elevation of the body temperature induces blood flow redistribution to the skin [25] that leads to blood decline in central and other organs.…”
Section: Plos Onementioning
confidence: 99%